2008
DOI: 10.1075/eww.29.2.02deu
|View full text |Cite
|
Sign up to set email alerts
|

Mobile language choices — The use of English and isiXhosa in text messages (SMS)

Abstract: This paper looks at language choice and use in South African SMS communication (texting) among bilingual (isiXhosa / English-speaking) users. Although English is the preferred language for most of the 22 participants (aged between 18 and 27), SMSes also create a forum for isiXhosa literacy (either in isiXhosa messages or in mixed English-isiXhosa messages). The English-language SMSes produced by these bilingual speakers share many of the features which have been reported for English SMS communication internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 0 publications
6
51
0
10
Order By: Relevance
“…This finding supports the findings of Battestini et al (2010), Bosco (2007), Deumart andMasinyana (2008), andThurlow (2003). Most of the text messages were sent by the students to strengthen their alliances and cement their relationships with their text-circle, which includes close and intimate friends.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding supports the findings of Battestini et al (2010), Bosco (2007), Deumart andMasinyana (2008), andThurlow (2003). Most of the text messages were sent by the students to strengthen their alliances and cement their relationships with their text-circle, which includes close and intimate friends.…”
Section: Discussionsupporting
confidence: 91%
“…They include: informational-practical orientation (14%), informational-relational orientation (8%), practical-arrangement orientation (15%), social arrangement orientation (9%), salutory orientation (17%), friendship maintenance orientation (23%), romantic orientation (9%), sexual orientation (3%), and chain messages (2%). Deumart and Masinyana (2008) verified that the communicative functions found in their corpus were quite similar to those of Thurlow's. They pointed out, however, that the number of messages included under the category of practical/social arrangements are fewer than the ones mentioned by Thurlow (2.45%), and having more love-related messages and chain messages (19% and 7% compared to 12% and 2% respectively).…”
Section: What Do Young People Use Text Messaging For?supporting
confidence: 56%
“…It is with reference to 'counter-cultural' symbolism that has been cultivated by popular African-American artists and entertainers that scholars like Deumert and Masinyana (2008) suggest that the imitation of the AAVE accent exists, and influences the spelling of CMC texts produced by South African youths. This may certainly be true, from an anthropological perspective.…”
Section: Th Written As D or Fmentioning
confidence: 99%
“…A study by Deumert and Masinyana (2008: 117) on the patterns of language use in mobile messaging among young isiXhosa speakers, found that English is the preferred code for most of them, and that the majority of their messages conformed largely to they describe as 'a globalised SMS English norm'. Nevertheless, the messages also displayed local features both in terms of form and content (Deumert and Masinyana 2008). They further suggest that choosing isiXhosa and not abbreviating it comes at a direct cost (around 80 cents per message) to the bilingual user, and generally isiXhosa speakers reacted with puzzlement to the very idea of abbreviated SMS in isiXhosa (Deumert and Masinyana 2008).…”
mentioning
confidence: 92%
“…Nevertheless, the messages also displayed local features both in terms of form and content (Deumert and Masinyana 2008). They further suggest that choosing isiXhosa and not abbreviating it comes at a direct cost (around 80 cents per message) to the bilingual user, and generally isiXhosa speakers reacted with puzzlement to the very idea of abbreviated SMS in isiXhosa (Deumert and Masinyana 2008). Their findings show that young isiXhosa home language speakers prefer using https://repository.uwc.ac.za/ English in SMS communication since it is not easy to abbreviate isiXhosa, which occurs most commonly in code-mixed messages.…”
mentioning
confidence: 99%